In-Situ Sensor Response of Copper Oxide Urchin-like Structures - Orlandi, M. O. [UNESP]; Felix, A. A. [UNESP]; Suman, P. H. [UNESP]; Varela, J. A. [UNESP]; Volanti, D. P. [UNESP]; IEEE (Ieee, 2016)
In this work we report an advanced study of gas sensor performance of copper oxide (CuO) urchin-like structures synthesized by microwave assisted hydrothermal method. Copper oxide in an interesting p-type semiconductor in order to study the mechanisms related to the sensor response of CuO structures, we developed a special sample holder which enables the simultaneous characterization of materials by X-ray absorption near edge structure (XANES) and electrical measurements. Quantitative XANES analyses showed that the CuO material can have its surface completely reduced when exposed to H-2 in N-2 baseline and electrical measurements confirm the abrupt decrease in the material resistance. This superficial reduction is reversible after exposition of sample to a synthetic air atmosphere. Sensor response models for CuO material based on these findings were proposed.
Keywords: Sensors; copper oxide; nanomaterials